PENGARUH FASILITAS BELAJAR SISWA, MOTIVASI BERPRESTASI DAN CARA BELAJAR TERHADAP HASIL BELAJAR PADA SISWA KEAHLIAN AKUNTANSI SMK NEGERI KOTA PADANG - Devi Edriani (PAKAR Pendidikan, 2017)
This research aims to analyze and see the effect of student learning facilities, achievement motivation and learning styles of the students’ on learning outcomes on student accounting Expertise SMK Padang City. This research is descriptive and associative. The study population all students of Accounting at SMK Padang numbering 822 people, the number of samples 270 people. The sample technique proportionally stratified random sampling. Data and data sources are primary data in the form of a questionnaire filled by the respondents, as well as secondary data about student learning outcomes obtained from documentation. The test instrument validity and reliability. Analyzed using descriptive and inductive analysis, ie test for normality, homogeneity test and test hypotheses using path analysis, F test and t test. The results showed that: 1) Facilities student learning significantly influence student achievement motivation, 2) Facilities student learning and achievement motivation significantly influence to learning styles of syudents, 3) Facilities student learning, achievement motivation and learning styles have a significant and contribution on students’ learning outcomes in Accounting Expertise SMK Padang